Implementation of Independent Teaching and Independent Play in Fostering Religious Feelings in 5-6 Year Old Children - Agustina Dewi Rahayu; Yuli Kurniawati Sugiyo Pranoto (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The implementation of independent teaching and independent play in the Independent Curriculum is expected to help achieve learning objectives. The Integrated Islamic Kindergarten Institution, under the auspices of the Integrated Islamic School Network (JSIT), also collaborates the Integrated Islamic School Network (JSIT) Curriculum with the Independent Curriculum, which hopes to develop children's potential and instill religious values. The purpose of this study is to determine how the implementation of independent teaching and independent play can foster religious feelings in children aged 5–6 years at the City of Semarang Integrated Islamic Kindergarten. The research method used is qualitative, with data analysis techniques using the Miles and Huberment model, namely data reduction, data display (data presentation), and conclusion drawing. The results of the study show that independent teaching gives teachers the freedom to manage the class, providing child-centered learning. Through independent play, children's play rights are fulfilled, and children feel happy. In terms of fostering children's religious feelings, teachers and parents collaborate to instill the habit of worship and give confidence that Allah SWT is the God of Muslims. The implementation of freedom of teaching and freedom of play with fun activities, habituation of worship activities, and collaboration with parents is able to foster children's religious feelings who are still in the learning stage. Keywords:  Independent Teaching, Independent Play, Religious Feelings